Divisia monetary aggregates for a heterogeneous euro area - Maximilian Brill; Dieter Nautz; Lea Sieckmann (Freie Universität Berlin, School of Business & Economics, 2019)
We introduce a Divisia monetary aggregate for the euro area that accounts for the heterogeneity across member countries both, in terms of interest rates and the decomposition of monetary assets. In most of the euro area countries, the difference between the growth rates of the country-specific Divisia aggregate and its simple sum counterpart is particularly pronounced before recessions. The results obtained from a panel probit model confirm that the divergence between the Divisia and the simple sum aggregate has a significant predictive content for recessions in euro area countries.
urn:nbn:de:kobv:188-refubium-24962-2
Keywords: E51; E32; C43; 330; Monetary aggregation; Euro area Divisia aggregate; Recessions